Pertunjukan Liong dan Barongsai di Yogyakarta: Redefinisi Identitas Tionghoa - -, Sudono; -, Suhartono; Simatupang, GR Lono Lastoro (PANGGUNG, 2013)
ABSTRACTÃÂ Since the reformation era, the Indonesian Chinese get their rights as citizens of the nation of IndoÃÂ nesia. They earn the right to live as citizens as the other nations in Indonesia, including the practice of their religion and belief, as well as their culture. Nevertheless, political discrimination of the New Order government for three decades had created blockage impact on cultural transfer from one geneÃÂ ration to the next. Today, when they get their freedom, the process of commodification of culture also played a role in redefining their identity. This study aims at determining how they define their identity. This study used a qualitative descriptive approach. The technique of collecting data used literature study, observations and inÃÂdepth interviews. The result of the study shows that commoÃÂ dification of Chinese culture does not make the vanishment of their identity and culture, but it has strengthened the Chineseness and created the emergence of the new texts on Liong and Barongsai culture.ÃÂ Keywords: Liong, Barongsai, redefinition of Chinese identityÃÂ ÃÂ ABSTRAKÃÂ Sejak lahirnya reformasi, orang Tionghoa Indonesia memperoleh hak mereka sebagai war- ga bangsa Indonesia. Hak hidup sebagaimana warga bangsa lainnya di Indonesia telah mereka peroleh kembali, termasuk menjalankan agama dan kepercayaan, serta budaya mereka. Namun demikian, kebijakan diskriminatif pemerintah Orde Baru selama tiga da- sawarsa berdampak pada tersumbatnya transfer budaya dari generasi ke generasi beri- kutnya. Kini, ketika kebebasan tersebut didapat, proses komodifikasi budaya juga ikut berperan dalam mendefinisikan identitas mereka kembali. Penelitian ini bertujuan untuk mengetahui bagaimana mereka mendefinisikan identitas mereka. Penelitian ini meng- gunakan pendekatan kualitatif deskriptif. Teknik pengambilan data menggunakan studi literatur, pengamatan dan wawancara mendalam. Hasil penelitian menunjukkan bahwa komodifikasi atas budaya Tionghoa tidak bermuara pada matinya identitas dan hilangnya kebudayaan Tionghoa, tetapi justru telah memperkuat ke-Tionghoaan dan juga muncul- nya teks-teks baru pada produk budaya Liong dan Barongsai.ÃÂ Kata kunci: Liong, Barongsai, redifinisi identitas Tionghoa